Increasing Hydrolytic Activity of Lipase on Palm Oil by PCR-Based Random Mutagenesis - Maria Dita Febriani Lumban Gaol; Andreas Adhi Satya; Esti Puspitasari; Nisa Rachmania Mubarik; Antonius Suwanto (International Journal of Oil Palm, 2020)
ABSTRACT Random mutagenesis technique is a powerful technique capable of producing enzymes with desired biocatalytic activity. This study aims to obtain a mutant lipase with improved hydrolytic activity on palm oil substrate using random mutagenesis technique. Random mutagenesis by error-prone PCR was used to generate mutant lipases. A total of 1101 mutants were obtained, out of which two mutants, Lip M14.25, and Lip M14.57, showed an increased relative hydrolytic activity. Lip M14.25 and Lip M14.57 demonstrated a 14% and 16% increased activity respectively. A comparison of the mutants' hydrolytic activities using p-nitrophenyl esters showed a significantly high preference for p-nitrophenyl palmitate. Furthermore, the mutant, Lip M14.25 showed its highest activity at pH 5, and Lip M14.57 exhibited a 10 oC decrease in optimum temperature. The two mutants' protein modelling showed the substitution of N44S/S202N on M14.25 and F154L/S265C on M14.57 lipase, which caused changes in conformation and active site residue distance of the lipase. The study found two mutants of lipase, M14.25 and M14.57, which showed improved hydrolytic activity on palm oil substrate.